Antibiotic resistance evolution of Pseudomonas aeruginosa in cystic fibrosis patients (2010‐2013). (1st April 2018) - Lucca, Francesca; Guarnieri, Margherita; Ros, Mirco; Muffato, Giovanna; Rigoli, Roberto; Da Dalt, Liviana
Abstract: Introduction: Pseudomonas aeruginosa is the predominant pathogen responsible of chronic colonization of the airways in cystic fibrosis (CF) patients. There are few European data about antibiotic susceptibility evolution of P aeruginosa in CF patients. Objectives: The aim of this study is to evaluate the evolution of antibiotic resistance in the period 2010‐2013 in CF patients chronically colonized by P aeruginosa and to highlight the characteristics of this evolution in patients younger than 20 years. Methods: Clinical and microbiological data were extracted from two electronic databases and analyzed. Antibiotic resistance was defined according to European Committee of Antimicrobial Susceptibility Testing for levofloxacin, ciprofloxacin, meropenem, amikacin and ceftazidime. The between‐group comparison was drawn with the Chi‐square test for proportions, with the T ‐test for unpaired samples for normally distributed data and with Mann‐Whitney test for non‐normally distributed data. Significancy was defined by P  < .05. Results: Fifty‐seven CF patients, including thirteen subjects aged less than 20 years, were enrolled. P.. aeruginosa antibiotic sensitivity decreased significantly for fluoroquinolones, mainly in patients aged <20 years, while it increased for amikacin and colistin. The analysis of minimum inhibitory concentration confirmed these trends. In pediatric patients treated with more than three antibiotic cycles per year, greater resistance was found, except for amikacin and colistin. Conclusion: An evolution in P aeruginosa antibiotic resistances is observed in the 4‐year period studied. Responsible and informed use of antibiotics is mandatory in CF.